Adrenomedullin regulates the speed of oviductal fluid flow in cattle. Issue 8 (11th July 2017) - Yoshimoto, Yuka; Nishie, Takumi; Ito, Sayaka; Kobayashi, Yoshihiko; Yamamoto, Yuki; Okuda, Kiyoshi; Kimura, Koji
Abstract : Unidirectional flow of oviductal fluid from the ovarian to uterine side of the ampulla plays a significant role in successful pregnancy, and is produced by ciliary beating. Various systems regulate ciliary beating, such as paracrine, autocrine, and endocrine. We hypothesized that Adrenomedullin (ADM)—a peptide hormone that acts via its receptors, which are complexes of Calcitonin receptor‐like receptor (CRLR) and Receptor activity‐modifying protein (RAMP) 2 or 3 — promotes oviductal fluid flow in the ampulla of bovine oviducts. First, we examined the expression of ADM, CRLR, RAMP2, and RAMP3 mRNAs in isolated epithelial cells throughout the estrous cycle, and the localization of ADM receptor protein constituents in the ampulla. RAMP2 expression was significantly higher in the follicular phase. Furthermore, RAMP2 protein was detected only in ciliated cells, whereas CRLR and RAMP3 were detected in all epithelial cells. The effects of ADM and an ADM antagonist on fluid‐flow speed were examined using microbeads in ampullary tissue. ADM antagonist decreased bead transport speed, and this decrease was reversed by ADM. In addition, ADM recovered the bead transport speed that decreased in the absence of calcium. Overall, our results suggest that ADM contributes to the regulation of oviductal fluid flow in ampulla.